The Response of a Highly Skewed Steel I-Girder Bridge with Different Cross-Frame Connections - Almoosi, Y.; Oukaili, N. (Engineering, Technology & Applied Science Research, 2021)
Braces in straight bridge systems improve the lateral-torsional buckling resistance of the girders by reducing the unbraced length, while in horizontally curved and skew bridges, the braces are primary structural elements for controlling deformations by engaging adjacent girders to act as a system to resist the potentially large forces and torques caused by the curved or skewed geometry of the bridge. The cross-frames are usually designed as torsional braces, which increase the overall strength and stiffness of the individual girders by creating a girder system that translates and rotates as a unit along the bracing lines. However, when they transmit the truck’s live load forces, they can produce fatigue cracks at their connections to the girders. This paper investigates the effect of using different details of cross-frames to girder connections and their impacts on girder stresses and twists. Field testing data of skewed steel girders bridge under various load passes of a weighed load vehicle incorporated with a validated 3D full-scale finite element model are presented in this study. Two types of connections are investigated, bent plate and pipe stiffener. The two connection responses are then compared to determine their impact on controlling the twist of girder cross-sections adjacent to cross-frames and also to mitigate the stresses induced due to live loads. The results show that the use of a pipe stiffener can reduce the twist of the girder’s cross-section adjacent to the cross-frames up to 22% in some locations. In terms of stress ranges, the pipe stiffener tends to reduce the stress range by 6% and 4% for the cross-frames located in the abutment and pier skew support regions respectively.